CME providers’ experiences and practices in Pakistan: a case study - Farhan Saeed Vakani; Apo Demirkol; Kerry Uebel; Chinthaka Balasooriya (BMC Medical Education, 2024)
Abstract Background Pakistan has made numerous attempts to establish and implement a national mandatory CME program which currently do not exist. The purpose of this study is to explore the views of major CME providers in order to identify possible strengths and weaknesses in the current program, and offer evidence-based recommendations to help further enhance the national CME program in Pakistan. Methods An exploratory study design using a case study approach through in depth interviews was conducted to examine CME providers’ experiences and perceptions. The study was conducted in Pakistan between August and November 2019 with CME providers from Sindh, Punjab, the North-West Frontier Province, and the Federal Capital Territory. Thirty-six providers recognised by the Pakistan Medical and Dental Council who were involved in providing CME activities at the national level and whose contact information was publicly available on their websites, were selected for the study. Of the 36 providers invited, 22 participated in this study. Results The results generated several organising themes grouped into three major themes: (1) CME current practices, (2) CME past experiences, and (3) Future developments. Conclusion Participants recommended needs-based educational activities for physicians, a well-structured central regulatory CME body collaborating with existing providers, involving experienced providers for rural CME, accrediting diverse local providers, limiting commercial entities’ role, and implementing CME with proper preparation and a phased approach.